Controle e autonomia nas gestões Kirchner e Fernández de Kirchner (2003-2011): a Argentina na construção do Conselho de Defesa Sul-Americano - Pereira, Matheus de Oliveira [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
The dissertation deals with Argentina's foreign and defense policies between 2003 and 2011, analyzing the meaning of country's participation in the construction of the Council of South American Defense. We worked with the hypothesis that Argentina's adherence and action in the CDS can be understood in light of the attention to a set of the country's interests, both from an internal viewpoint and internationally. The main argument can be summarized in three faces: 1) the setting of civil control and international cooperation in the practice of defense policy; 2) a diplomatic action driven in search for higher margins of autonomy, interpreted through a specific lens; 3) the particular logic of Argentine-Brazilian relations. An additional propose of interpretation is offered, considering the interest of Argentinian government in exercise of a leadership based on the regionalization of a set of normative definitions in the defense field. In this work, we adopt an approach that combines history and conjuncture, based on literature review and empirical research from primary sources.

A dissertação aborda as políticas externa e de defesa da Argentina entre 2003 e 2011, perquirindo o significado da participação do país no Conselho de Defesa Sul-Americano para essas duas dimensões. Trabalhamos com a hipótese que a adesão e a forma da atuação da Argentina no CDS podem ser compreendidas à luz da atenção a um conjunto de interesses do país tanto do ponto de vista interno como internacional. Nesse sentido, o argumento apresentado possui três aspectos principais: 1) a cristalização do controle sobre os militares e da cooperação internacional na práxis da defesa; 2) uma ação diplomática voltada a obter maior autonomia, sem que isso implique em confrontação ou ruptura nas relações exteriores; 3) a lógica própria das relações argentino-brasileiras. Apresenta-se ainda uma possibilidade interpretativa para a atuação do país no CDS: o de exercício de uma posição de liderança a partir da regionalização de um conjunto de definições normativas no campo da defesa. No trabalho, adota-se uma abordagem que combina história e conjuntura, realizada a partir de revisão bibliográfica e pesquisa empírica a partir de fontes primárias.
Control and autonomy in Kirchner and Fernández de Kirchner's government (2003-2011): Argentina and the construction Council of South America Defense
Keywords: Defense policy; Foreign policy; South-American Council of Defense; Argentina; Política de defesa; Política externa; Conselho de Defesa Sul-Americano